Effects of sea urchin (Diadema setosum) gonad extracts on gene expression of FOXP3 and the production of cytokine on Salmonella typhi-induced mice - Wa Ode Salma, Sitti Wahyuni, Nursin Kadir, Suryani Asad, Irawan Yusuf (Journal of Applied Pharmaceutical Science, 2018)
The gonad of the sea urchin, Diadema setosum, is highly nutritious and has demonstrated the importance for the regulation of inflammation response. However, no previous research study has evaluated the capacity of sea urchin gonads to regulate the inflammatory response. Our objectives were to examine the effect of gonad extracts of D. setosum on the expression of mRNA FoxP3 gene and the production of cytokine interferon-gamma (IFN-g) and interleukin-10 (IL-10) in mice after the induction of lipopolysaccharide (LPS) using Salmonella typhi. Fifteen male mice were divided into two groups (intervention and control), before and after intraperitoneal injection of S. typhi. The intervention group was treated with two dosages of the extracted gonad (100 and 200 mg/kg of body weight). The control group was fed with the natural diet only. We found that the expression of gene FoxP3 and production of cytokine exhibited a short decrease after 24 hours of LPS induction and then returned to pre-induction levels. Notably, the expression of FoxP3 and production of IFN-g in the control group continued to decline significantly until day 7. Conversely, the production of IL-10 continued to increase significantly. We conclude that the gonad extract of D. setosum is effective for the regulation of immune response and it has strong potential to be developed as a dietary supplement for acute and chronic inflammation.
Keywords: Diadema setosum, gonad, mRNA FoxP3, cytokine, Salmonella typhi.